Book Review - The Short Bus: A Journey Beyond Normal - Mehrenberg, Richard L. (Journal of the American Academy of Special Education Professionals, 2007)
The Short Bus: A Journey Beyond Normal is a colorful and revealing series of case studies with individuals generally considered "different" by society. Author, Jonathan Mooney traveled cross-country to seek out people who celebrate what others consider disabilities and to tell their tales. The stories they share are funny, enlightening and just as unique as the people who tell them.